Comparison of two picosecond lasers to a nanosecond laser for treating tattoos: a prospective randomized study on 49 patients. (21st August 2017) - Lorgeou, A.; Perrillat, Y.; Gral, N.; Lagrange, S.; Lacour, J.‐P.; Passeron, T.
Abstract: Background: Q‐switched nanosecond lasers demonstrated their efficacy in treating most types of tattoos, but complete disappearance is not always achieved even after performing numerous laser sessions. Picosecond lasers are supposed to be more efficient in clearing tattoos than nanosecond lasers, but prospective comparative data remain limited. Objective: To compare on different types of tattoos the efficacy of a nanosecond laser with two types of picosecond lasers. Methods: We conducted a prospective randomized study performed from December 2014 to June 2016 on adult patients with all types of tattoos. The tattoos were divided into two halves of equal size. After randomization, half of the tattoo was treated with a picosecond laser and the other half with a nanosecond laser. The evaluation was performed on standardized pictures performed before treatment and 2 months after the last session, by two physicians, not involved in the treatment, blinded on the type of treatments received. The main end point was a clearance above 75% of the tattoos. Results: A total of 49 patients were included. Professional tattoos represented 85.7%, permanent make‐up 8.2% and non‐professional tattoo 6.1%. The majority were black or blue and 10.2% were polychromatic. No patient was lost during follow‐up. A reduction of 75% or more of the colour intensity was obtained for 33% of the tattoos treated with the picosecond lasers compared to 14% with the nanosecond laser ( P = 0.008). An improvement superior to 75% was obtained in 34% monochromic black or blue tattoos with the picosecond lasers compared to 9% for the nanosecond laser. Only one of the five polychromic tattoos achieved more than 75% of improvement with the two types of laser. Conclusion: Our results show a statistically significant superiority of the picosecond lasers compared to the nanosecond laser for tattoo clearance. However, they do not show better efficacy for polychromic tattoos and the difference in terms of side‐effects was also minimal with a tendency of picosecond lasers to be less painful.